66PDual inhibition of TGF-β and AXL as a novel treatment for colorectal cancer. (1st October 2019) - Ciardiello, D; Belli, V; Cardone, C; Vitiello, P P; Martini, G; Poliero, L; Borrelli, C; Arrichiello, G; Ciaramella, V; Matrone, N; Barra, G; De Falco, V; et al.
Abstract: Background: AXL and transforming growth factor β (TGF-β) signalling pathways play a key role in modulating tumour microenvironment by promoting epithelial to mesenchymal transition (EMT), stromal activation and regulating immune response in colorectal cancer (CRC). Here we have evaluated the effect of double blockade of TGF-β and AXL receptors, as an innovative therapeutic strategy for CRC. Methods: We assessed the correlation of TGF-β and AXL by an in silico analysis of a human CRC gene expression profile database. Afterwards, an evaluation of AXL expression of in a panel of human CRC cell lines by Western Blot (WB) and Real time PCR was performed. The sensitivity of HCT116 and LOVO cells to treatment with galunisertib (LY21209761), a TGF-β R1 inhibitor, and R428, an AXL inhibitor, was assessed by MTT, cell migration, and colony forming assays. Furthermore we generated patient derived 3D spheroid cultures from primary CRC, and tested their susceptibility to galunisertib and R428 by MTT assay. Finally, in vivo experiments were done with HCT116 and LOVO tumour xenografts in immunodeficient mice. Results: In silico analysis showed an association between high expression levels of AXL and TGF-β R1 in CMS4 CRC. AXL was differently expressed on cell lines, and interestingly it resulted increased in HCT116 and LOVO after TGF-β inhibition, probably representing a mechanism of cancer cell escape. Dual blockade with galunisertib and R428 determined a reduction in cell migration of 50% in HCT116 and 37% in LOVO cells, respectively, and colony formation of approximately 90 % in both cell lines. Moreover, combined treatment displayed a strong synergistic activity in 3D cultures derived from five human CRC samples, resulting in the inhibition of proliferation ranging from 80 to 90%. The in vivo experiments of HCT116 and LOVO subcutaneous xenograft models are currently on going and results will be presented. Conclusions: Combined TGF-β and AXL inhibition showed a promising activity in preclinical models of CRC and could represent a novel potential therapeutic strategy for patients with CRC. Legal entity responsible for the study: Università degli studi della Campania "Luigi Vanvitelli". Funding: ICURE project, Università degli studi della Campania "Luigi Vanvitelli". Disclosure: D. Melisi: Research grant/Funding (self): Lilly.